Developing New Masters Program on Library and Information Science for the LIS Faculties of Armenia, Georgiaand Uzbekistan - Hopkinson, Alan; Zargaryan, Tigran (Infotheca - Journal for Digital Humanities; Vol 10 No 1/2 (2009): Infotheca - Journal of Informatics and Librarianship, 2024)
Starting from January 2009 six organizations from Armenia, Georgia and Uzbekistan in partnership with the European Union universities are participating in a three year multi-national joint European project “Developing New Masters Programme in Library and Information Science”, funded and managed by the European Union “Tempus-Tacis” programme. LIS education in these three republics needs root-and-branch modernization, as the existing curricula are in their form, content and teaching approaches still based on the 1960s practices. The lectures are heavily overloaded with the Soviet library management traditions, which are already outdated. The curricula to be developed will be based on accepted best practice in European partner Universities’ LIS faculties, and it is anticipated that the subjects will meet the requirements of the Bologna and related agreements. Lifelong learning component and advanced skills courses will also be introduced. In the European Union, many library schools also teach archival studies. The discipline is increasingly sharing modules with library and information science in the electronic age so this has also been included in the project. Implementation of the new curricula will directly affect assist in building ‘Knowledge Societies’ in these three former Soviet republics.